Gestern gings noch, Herr Schürmann - Krämer, Jan (Germany : FreudeFilm ; Ruhrkomplex Film, 2016)
'This is the third and most interesting part of my life', said Mr Schurmann. He is wandering through hospital corridors, searching for new tasks. In former times, Mr Schurmann read, he enjoyed taking pictures and filming. His new world is rather clean and cold however, and he is surrounded by the atmosphere of a hospital with patients who might never leave. For two months, he has lived in a closed nursing home for people suffering with dementia. 'I don’t recognise my own logic, something exploded. We have to support each other. Because, the first does not know why, the second does not participate and the third one knows how it works.'
Verzio Film Festival Submission
Keywords: Documentary films